2010
DOI: 10.1021/ic101602a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Bifunctional Gas Sensing Properties of Porous In2O3−CeO2 Binary Oxide Nanotubes

Abstract: The porous binary In(2)O(3)-CeO(2) oxides nanotubes (NTs) in cubic phase were first fabricated by electrospinning (ESP) method and characterized by SEM, TEM, XRD, XPS and UV-vis absorption techniques. By adjusting the In(2)O(3) and CeO(2) molar ratio, the out diameters and wall thicknesses of the final composites were tuned ranging of 90-180 nm and 15-9 nm, respectively. The band gap of the binary oxides gradually decreases, and the ratio of Ce(3+) to Ce(4+) increases with the increase of CeO(2), implying that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 46 publications
1
54
0
Order By: Relevance
“…Indium oxide (In 2 O 3 ) belongs to the class of wide-bandgap metal oxides, which represents an important class of gas-sensing materials for detecting harmful gases, such as H 2 S, NH 3 , and NO x [37]. It has been demonstrated that a decrease in size of the In 2 O 3 crystallites in the sensing layer can considerably enhance the response [38].…”
Section: Introductionmentioning
confidence: 99%
“…Indium oxide (In 2 O 3 ) belongs to the class of wide-bandgap metal oxides, which represents an important class of gas-sensing materials for detecting harmful gases, such as H 2 S, NH 3 , and NO x [37]. It has been demonstrated that a decrease in size of the In 2 O 3 crystallites in the sensing layer can considerably enhance the response [38].…”
Section: Introductionmentioning
confidence: 99%
“…But the SnO 2 nanoparticles were not evenly distributed on the surface of WO 3 lamella. In 2 O 3 is also a promising gas-sensing material especially to detect H 2 S. [33][34][35][36][37][38][39] The combination of WO 3 and In 2 O 3 nanocrystals, i.e., In 2 O 3 /WO 3 composite, can be expected to be an efficient gas-sensing system for gas detection but the In 2 O 3 /WO 3 composites reported were fabricated by simply mixing the solid-state precursor powders. 40,41 The microstructural control of the second phase is not available, and it is still a big challenge to achieve hierarchical In 2 O 3 /WO 3 nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Among these materials, there is a great interest in the synthesis of semiconductor oxides [2,3] and transition metal oxides [4], which can be used in extensive applications such as gas sensors, photochromic devices, and magnetic materials. Especially, various mixed transition metal oxides have been found very attractive in catalysis field [5].…”
Section: Introductionmentioning
confidence: 99%